Community Engagement: Building, Maintaining, and Facilitating Engagement Between Veterans and Researchers - Ashley Gendrett; Adrian Rideau; Drew Helmer; Nipa Kamdar (The University of Alabama, 2024)
Researchers acknowledge the importance of community engagement as a pathway to understand needs, build rapport, and empower community members to impact change. Within the Department of Veterans Affairs, community engagement is largely facilitated through veteran engagement groups (VEGs). Veteran engagement groups consist of veterans from diverse backgrounds who work with researchers to develop and implement studies that will be relevant to the veteran population. In this paper, we share the processes used to build, maintain, and facilitate engagement between veterans and researchers. We also share some of the challenges we continue to face as a group.